The Rector's Transformational Leadership Style at Nahdhatul Ulama College: Kepemimpinan Tranformasional Rektor Di Perguruan Tinggi Nahdlatul Ulama - Wakit , Saipul; Dacholfany, Muhammad Ihsan; Wahab, Abdul; Muhja, Zainal Abidin; Suharyat, Yayat; Nursikin, Mukh; Supriatna, Dasep (Universitas Muhammadiyah Sidoarjo, 2022)
To maintain the existence and sustainability of higher education institutions requires a leader, namely a chancellor who is able to seize opportunities and read situations that are challenges far ahead, so that a chancellor has an important and strategic role in managing the institution. in the context of leadership that aims at the direction of rapid progress and change is transformational. So that the leadership style is very relevant to be used as a basis and studied scientifically. Practically in this article, it will be explained about the transformational leadership of the rector in the Nahdlatul Ulama tertiary institution which substantially examines how the rector provides exemplary, motivational, intellectual stimulation and consideration with subordinates in the higher education environment. The research method uses a qualitative approach with a case study model at Nahdlatul Ulama University. As for data collection techniques using observation, documentation and interviews. As for the data analysis using the preposition technique between the findings and the theory used. The results of the research explain that the transformational leadership of the rector in private tertiary institutions includes 1) exemplary which is manifested through uswah hasanah, morals, work and work ethic, 2) motivation is carried out in two ways, namely orally and in writing, while the mechanism is carried out through formal and non-formal forums. formal, 3) stimulation carried out by the chancellor by giving itibar or inspirational stories to work well and sincerely to advance the Institution, while 4) consideration is carried out through humane relations with all elements within the Institution by prioritizing kinship and mutual care, compassion and care.